2012
DOI: 10.1007/s11135-012-9771-7
|View full text |Cite
|
Sign up to set email alerts
|

Passenger satisfaction: a multi-group analysis

Abstract: To analyse the level of passenger satisfaction of a public local transport service, after an explorative factorial analysis, a Structural Equation Model was adopted. The main goal of this paper is to verify how much some service characteristics could influence the perceived quality of the service. The passengers are found very sensitive to the level of the service organization and to the way the service is delivered (punctuality and regularity, and short waiting time). The safety and reliability of buses, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…According to (Oña et al, 2013) and (Antonucci et al, 2014), passenger satisfaction with public transport can be grouped into a number of latent variables consisting service organization, safety, and reliability, human resources and comfort, and cleanliness.…”
Section: Public Transport Passenger Satisfactionmentioning
confidence: 99%
“…According to (Oña et al, 2013) and (Antonucci et al, 2014), passenger satisfaction with public transport can be grouped into a number of latent variables consisting service organization, safety, and reliability, human resources and comfort, and cleanliness.…”
Section: Public Transport Passenger Satisfactionmentioning
confidence: 99%
“…Antonucci et al (2014) propose a model that assumes that customer satisfaction, measured starting from the variable ''overall satisfaction'', is determine by many unobservable latent factors, such as service organization, safety and reliability, comfort and cleanliness, and human resources. Satisfaction in this study is regarded as comprising two parts-satisfaction with facilities and service satisfaction.…”
Section: Satisfaction With Facilitiesmentioning
confidence: 99%
“…In de Oña, de Oña, Eboli and Mazzulla (2013) and also in Antonucci, L. et al (2014) there was the method of structural equation modelling applied in order to measure passengers' satisfaction with public city transport services and in order to verify how much some service characteristics could influence the perceived quality. All these authors claim that factors affecting customer satisfaction with public city transport can be grouped into latent variables consisting service organisation, safety and reliability, human resources and comfort and cleanliness.…”
Section: Theoretical Background Of the Users´ Satisfaction Measurementmentioning
confidence: 99%
“…It is important to note that these results are useful only for Spanish public transport services because the respondents of this research were only passengers of the bus transit services in Spain (de Oña, de Oña, Eboli & Mazzulla, 2013). Antonucci, L. et al (2014) applied in their study an explorative factorial analysis and a structural equation model and they found that the Italian passengers are very sensitive to the level of the service organization and to the way the service is delivered. It means the punctuality and regularity and short waiting time are very important factors determining the customer satisfaction.…”
Section: Theoretical Background Of the Users´ Satisfaction Measurementmentioning
confidence: 99%
See 1 more Smart Citation